2013
DOI: 10.1155/2013/795458
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Dermal Substitute and Chitosan Skin Substitute Contribute to Accelerated Full-Thickness Wound Healing in Irradiated Rats

Abstract: Wounds with full-thickness skin loss are commonly managed by skin grafting. In the absence of a graft, reepithelialization is imperfect and leads to increased scar formation. Biomaterials can alter wound healing so that it produces more regenerative tissue and fewer scars. This current study use the new chitosan based biomaterial in full-thickness wound with impaired healing on rat model. Wounds were evaluated after being treated with a chitosan dermal substitute, a chitosan skin substitute, or duoderm CGF. Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…A significant problem with using collagen as the main component of scaffolds for skin substitutes is it has relatively poor mechanical properties[33]. However, these properties can be improved with various cross-linking methods, typically cross-linking collagen with glycosaminoglycans[3436], but also with hyaluronic acid[37], fibrin[38], chitosan[30,39,40], gelatin[41,42], elastin[43], pullulan[4446], alginate[47,48], laminin[49], poly(L-lactic acid) (PLLA)[50], poly(glycolide-co-L-lactide) (PLGA)[51,52], poly(ethylene glycol) (PEG)[53], and polycaprolactone (PCL)[54]. …”
Section: Components Of a Skin Substitutementioning
confidence: 99%
See 1 more Smart Citation
“…A significant problem with using collagen as the main component of scaffolds for skin substitutes is it has relatively poor mechanical properties[33]. However, these properties can be improved with various cross-linking methods, typically cross-linking collagen with glycosaminoglycans[3436], but also with hyaluronic acid[37], fibrin[38], chitosan[30,39,40], gelatin[41,42], elastin[43], pullulan[4446], alginate[47,48], laminin[49], poly(L-lactic acid) (PLLA)[50], poly(glycolide-co-L-lactide) (PLGA)[51,52], poly(ethylene glycol) (PEG)[53], and polycaprolactone (PCL)[54]. …”
Section: Components Of a Skin Substitutementioning
confidence: 99%
“…A few studies have shown positive wound healing effects from chitosan-based hydrogels[30,39,40]. Chitosan hydrogels have also been used in controlled release drug formulations due to its non-toxicity and structural stability[65].…”
Section: Components Of a Skin Substitutementioning
confidence: 99%
“…Through our experience in mouse model,[ 10 ] a diameter of 5 mm was considered the maximum. There has been a rat model using 1 x 1 cm wounds on the dorsum, inside a field of “photon beam” irradiation,[ 15 ] however, the “photon beam” described in this study may be an electron beam. As electron beams do not penetrate deeply, the tissue beneath the wound may have been intact.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 summarizes attempts to generate artificial skin grafts capable of reconstruction of skin appendages, pigmentation, and nerves. Mohd Hilmi et al [107] incorporated human fibroblasts and hair follicle stem cells into the chitosan skin substitute that was subsequently transplanted into a full-thickness wound in an irradiated rat model with impaired healing and hair loss. They observed that the applied cellular skin graft accelerated skin regeneration and was able to supply viable follicle stem cells into the irradiated wound.…”
Section: Reconstruction Of Skin Appendages Pigmentation and Nerves mentioning
confidence: 99%